2019
DOI: 10.1136/gutjnl-2017-315318
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a-1–5p increases CDX2 by targeting FOXD1 in bile acids-induced gastric intestinal metaplasia

Abstract: Background and aimsGastric intestinal metaplasia (IM) is common in the gastric epithelium of patients with chronic atrophic gastritis. CDX2 activation in IM is driven by reflux of bile acids and following chronic inflammation. But the mechanism underlying how bile acids activate CDX2 in gastric epithelium has not been fully explored.MethodsWe performed microRNA (miRNA) and messenger RNA (mRNA) profiling using microarray in cells treated with bile acids. Data integration of the miRNA/mRNA profiles with gene ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 48 publications
2
74
0
Order By: Relevance
“…Recently, what attracts people's attention is the regulatory mechanism of CDX2 in intestinal differentiation. In a previous study, our group con rmed that increased miR-92 is involved in the upregulation of CDX2 and the downstream IM markers in gastric cells treated by BA [18]. Besides, our in vivo and in vitro experiments provided evidence that downregulation of miR-1 facilitated the formation of a positive feedback loop involving HDAC6/HNF4α and then stimulated CDX2 expression in BA-induced IM cells.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, what attracts people's attention is the regulatory mechanism of CDX2 in intestinal differentiation. In a previous study, our group con rmed that increased miR-92 is involved in the upregulation of CDX2 and the downstream IM markers in gastric cells treated by BA [18]. Besides, our in vivo and in vitro experiments provided evidence that downregulation of miR-1 facilitated the formation of a positive feedback loop involving HDAC6/HNF4α and then stimulated CDX2 expression in BA-induced IM cells.…”
Section: Discussionsupporting
confidence: 60%
“…At present, many studies have provided evidence that miRNAs participate in the development, differentiation and formation of the digestive tract, so it also exert great in uence in the occurrence of IM, such as miR-30, miR-194 and miR-490 [16,17]. Moreover, it should be noted that our team has successfully constructed a cell model of BA-induced gastric IM, and found that miR-92 promotes the expression of IM markers Caudal-related homeobox 2 (CDX2), Krüppellike factor 4 (KLF4) and VILLIN 1 (VIL1) by targeting FOXD1 [18]. We also discovered that miR-1 was signi cantly reduced in tissues of patients with IM and cell models of BA-induced IM, as well as the reduction of which promoted the signi cant increase of CDX2, MUC2, KLF4 via targeting both HDAC6 and HNF4α (manuscript submitted for publication).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Relationship between miRNAs and GC has been reported in the previous studies [25]. For example, miR-92a-1-5p could increase CDX2 by targeting FOXD1 and mediate gastric intestinal metaplasia [26]. MiR-143-3p may inhibit GC growth and be more sensitive to cisplatin by targeting BRD2 [27].…”
Section: Discussionmentioning
confidence: 83%
“…Clinical researches indicated that bile acids (BAs) concentrations in gastric juice were positively correlated with the degree of IM regardless of Hp infection 7 , both in antrum 8 and cardia 9 . Our previous study first uncovered that BAs exposure could significantly induce gastric epithelial cells columnar genes expression through microRNA-mRNA networks involving a miR-92a-5p/ FOXD1/nuclear factor-κB (NF-κB) axis 10 . These results verified the key role of BAs reflux in gastric IM initiation and progression.…”
Section: Introductionmentioning
confidence: 99%